2013
DOI: 10.1007/s12013-012-9506-3
|View full text |Cite
|
Sign up to set email alerts
|

Phagocytized Beads Reduce the α5β1 Integrin Facilitated Invasiveness of Cancer Cells by Regulating Cellular Stiffness

Abstract: Cell invasion through the extracellular matrix (ECM) of connective tissue is an important biomechanical process, which plays a prominent role in tumor progression. The malignancy of tumors depends mainly on the capacity of cancer cells to migrate and metastasize. A prerequisite for metastasis is the invasion of cancer cells through connective tissue to targeted organs. Cellular stiffness and cytoskeletal remodeling dynamics have been proposed to affect the invasiveness of cancer cells. Here, this study investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 70 publications
0
14
0
Order By: Relevance
“…An effect similar to interference with Rac signaling was also observed upon addition of a Rac1 inhibitor to MDA-MB-231 human breast cancer cells, in which the invasiveness of Rac1 inhibitor-treated cancer cells was pronouncedly reduced after three days 54 . Indeed, we could confirm these results, as we performed 3D motility assays in the presence and absence of the Rac1 inhibitor EHT1864 using Rac1 fl/fl fibroblast cells.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…An effect similar to interference with Rac signaling was also observed upon addition of a Rac1 inhibitor to MDA-MB-231 human breast cancer cells, in which the invasiveness of Rac1 inhibitor-treated cancer cells was pronouncedly reduced after three days 54 . Indeed, we could confirm these results, as we performed 3D motility assays in the presence and absence of the Rac1 inhibitor EHT1864 using Rac1 fl/fl fibroblast cells.…”
Section: Discussionmentioning
confidence: 68%
“…Cell mechanical properties such as stiffness and the generation of contractile forces have previously been implicated in driving cell motility and invasion in a one to two mixture of rat and bovine collagen fiber matrices 44,50,5460 . Moreover, the deformability of cells measured with an optical cell stretcher correlates with their aggressiveness 47,6163 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After that time, beads were usually internalized by the cells. About 30 cells can be measured during the 40-min interval 57 .…”
Section: Methodsmentioning
confidence: 99%
“…Integrins are obligate heterodimers, which consist of αand β-subunits, in order to investigate whether Hsc70 affected integrin β1 specifically, the expression of the most common integrin α5 subunit was investigated. 14 As shown in Figure 2D and E, the results showed that both the mRNA level and protein expression on Hsc70-AS/U87 cell surface were not affected, suggesting the specificity of Hsc70 to integrin β1 subunit.…”
Section: Down-regulation Of Hsc70 In U87 Cells Promoted the Expressiomentioning
confidence: 80%